IDENTIFYING RISK FACTORS FOR STUNTING AMONG UNDER-FIVE INDONESIAN CHILDREN - Ayu, Mayang Sari; Rahmadhani, Mayasari; Pangestuti, Dewi; Ibarra, Florante (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
The prevalence of child stunting in Indonesia in 2023 at the national level from 24.5% to 21.6%. Despite declining, the figure is still relatively high, as 28 out of 100 babies suffer from stunting. The study aims to predict stunting risk factors in children under the age of 5. They use bivariate and multivariate logistic regression to identify significant factors associated with stunting risk. Stunting prevalence in Batu Bara District of North Sumatra Province was 18.35% out of 28.716 children under 5 years of age (967 children very short and 3,944 young children). The study was conducted on 100 households with brief and concise children living in rural areas. The results of the study showed maternal education (OR 5.27; 95% CI 1.04-5.62); low maternal nutritional status during pregnancy (OR 2.57, 95% CI 1.22-5.89); formula milk delivery less than 6 months (OR 3.47; 95% CI 1.40-8.28); low birth weight of less than 2500 grams (OR 4.94; 95% CI 1.30-18.80); lack of access to drinkable water (or 3.14; 95% CI 1.29-7.65); low family wealth index (OR 0.13; 95% CI 0.05-0.32). Environmental and household factors have a significant relationship with stunting risk control. Multilateral efforts from the level of family empowerment, increasing the role of health services, and improving nutritional status are access to public health status.